Adipocyte differentiation of 3T3-L1 cells under tenofovir alafenamide, tenofovir disoproxil fumarate, and integrase strand transfer inhibitors selective challenge: an in-vitro model. (15th March 2023) - Perna, Angelica; Carleo, Maria A.; Mascolo, Silvia; Guida, Alessandra; Contieri, Marcella; Sellitto, Carmine; Hay, Eleonora; De Blasiis, Paolo; Lucariello, Angela; Guerra, Germano; Baldi, Alfonso; De Luca, Antonio; et al.
Abstract : Objective: Integrase strand transfer inhibitors (INSTIs) are a class of antiretroviral therapy (ART) medications with a good tolerability profile and a high genetic barrier to HIV drug resistance. However, several studies report significant weight gain among persons receiving INSTI-based ART regimens compared with other regimens. Design: In-vitro model of adipogenesis. Methods: We used 3T3-L1 cells to investigate the effects of the nucleoside reverse transcriptase inhibitors (NRTIs) tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF), alone or in combination with INSTIs: raltegravir (RAL), elvitegravir (ELV), dolutegravir (DTG), and bictegravir (BIC) on adipose differentiation. To monitor adipocyte differentiation, expression levels of PPARɣ and C/EBPα and the intracellular lipid accumulation by Red Oil staining were used. Furthermore, we evaluated the immunohistochemical expression of ER-TR7, a fibroblastic marker, after INSTIs treatment. Results: Compared with control, INSTIs were able to increase adipogenesis, especially RAL and ELV. TAF and TDF inhibited adipogenesis alone and in combination with INSTIs. This ability was more evident when TAF was used in combination with DTG and BIC. Finally, INSTIs increased the expression of ER-TR7 compared with control and cells treated with TAF or TDF. Conclusion: Our data support the evidence that in-vitro challenge of 3T3-L1 cells with INSTIs is able to increase adipocytic differentiation and to drive a number of these cells toward the expression of fibroblastic features, with a different degree according to the various drugs used whereas TAF and TDF have an antagonistic role on this phenomenon.